PCR Technology and Its Importance In Covid-19 Pandemic - Maity, Anupam; Chakraborty, Krishnasis (Asian Journal of Pharmaceutical Research and Development, 2022)
Since the discovery of the PCR technology, its application in the various fields is increased gradually. Based on to this principle, many variations of the PCR have been established. Year by year, it is upgraded very much. It is established as a most common and accurate technique for the detection of the various diseases in the field of medicine. Now it is a ‘Gold standard’ for the detection of covid-19 also, which is much needed to contain the spread of the virus. Though various detection techniques are there for detection, but real time RT-PCR (variation of PCR) is most reliable. Viral detection is based on a simple principle of nucleic acid (viral) amplification. Various manufacturing companies are manufacturing the PCR instrument. Though the accuracy of the instruments are slightly differ to each other.